An Unprecedented View of Quantum Computers (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2023)
Every discussion of quantum computing starts with wave-particle duality, to explain how qubits differ from bits. But what if wave-particle duality were wrong? How would we explain quantum computing then? A little-known science called the Theory of Elementary Waves (TEW) says that quantum particles follow zero-energy waves backwards. Wave-particle duality cannot be true if waves and particles travel in opposite directions. This article proposes the first-ever TEW theory of quantum circuits. Elementary waves emanate from measuring devices and travel backwards through the circuits, whereas qubits move forwards through the wires and gates following those waves backwards. Quantum computers are known to be reversible. After we present that way-of-thinking, we will explain some of the evidence that TEW is valid. There is a mountain of empirical evidence from outside information technology. TEW is a maverick theory, out-of-step with the consensus about how quantum computers work. At first TEW sounds counterintuitive. Its advantage is Occam’s Razor: we present a simpler explanation of quantum circuits. We will present the quantum computer equivalent of saying that before the box is open Schrödinger’s cat is already dead or alive, but not both. Observing the cat simply tells us what was already true before we looked.